(untitled) (Fiep Bulletin - online, 2011)
This study aimed to evaluate the motor profile of children in relation to the skill levels of locomotion and object control. Study subjects were 62 students of 4 and 5 years old, seen in early childhood education program at the local Belém schools. To do so, we applied the Test of Gross Motor Development (TGMD-2) Ulrich (2000). In the locomotor subtest for 4 years old children, there was an improvement in the performance of boys (p-value = 0.0287 *). In the locomotor subtest for 4 years old children, boys showed higher levels of motor ability (p-value = 0.0051 *). In the locomotor subtest for 5 years old children, boys had higher levels of motor ability (p-value = 0.0065 *). TGMD-2 classification for every 4 years old child showed that 58.8% of girls and 71.4% of boys are in the category "medium", and this is the occurrence for both sexes (p-value = 0.3371). No evaluated child was classified as "above average", "superior" or "very superior". TGMD-2 classification for 5 years old children showed that 66.7% of girls and 63.6% of boys are in the category "average" which occurs in both sexes. The study concludes that children do not have advanced the level of development and the predominant profile was "average".